The Head Of Department's Strategy In Improving Civil Servant Performance In The Environmental Department Tabanan Regency (Strategi Kepala Dinas Dalam Meningkatkan Kinerja Pegawai Negeri Sipil Di Dinas Lingkungan Hidup Kabupaten Tabanan) - Artha Wibawa, I Ketut Sukantha (Universitas Panji Sakti, 2026)
This research aims to analyze the strategies implemented by the Head of the Tabanan Regency Environmental Agency to improve the performance of Civil Servants (PNS). The research focuses on leadership roles, including interpersonal, informational, and decisional roles. The research method used was a qualitative case study approach. Data collection was conducted through in-depth interviews, non-participant observation, and document review with the Head of the Agency, structural officials, and civil servants within the agency. The results indicate that the Head of the Agency has effectively implemented all three leadership roles. The strategies implemented include the application of participatory and transformational leadership styles, competency development through training, increased motivation through a reward system, and strengthening work culture and organizational communication. The implementation of these strategies has had a positive impact on improving discipline, responsibility, service quality, and organizational performance. However, several inhibiting factors exist, including budget constraints, variations in human resource (HR) quality, uneven employee discipline, suboptimal use of information technology, and complex bureaucratic procedures. This study concludes that the strategic role of the Head of the Department is crucial in creating a conducive work environment and improving civil servant performance through transformative leadership and appropriate HR development policies. Recommendations: Immediately prepare a data-driven and strategic proposal to advocate for increased funding to the Regency Government, particularly for training programs, procurement of work facilities, and a motivating incentive system.